2019
DOI: 10.1007/s11235-018-00542-8
|View full text |Cite
|
Sign up to set email alerts
|

Time division multiple access scheduling strategies for emerging vehicular ad hoc network medium access control protocols: a survey

Abstract: Vehicular Ad hoc Network (VANET) is an emerging and promising technology, which allows vehicles to communicate and share resources. These resources use applications that have to meet high reliability and delay constraints. However, to implement these applications, VANET relies on medium access control (MAC) protocol. Many approaches have been proposed in literature using Time Division Multiple Access (TDMA) scheme to enhance the efficiency of MAC protocol. Nevertheless, this technique is faced with some challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 81 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Thus, the TDMA protocols allocation strategies should take in consideration the mobility features to mitigate the problems of slot collisions. In Tambawal et al, 17 prominent TDMA‐based MAC protocols for vehicular networks were reviewed and compared based on the scheduling technique in solving the existing challenges. The authors have noted that the mobility features of VANETs is not well considered and the merging collision issue is not well addressed which resulted in a high delay and packet loss.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, the TDMA protocols allocation strategies should take in consideration the mobility features to mitigate the problems of slot collisions. In Tambawal et al, 17 prominent TDMA‐based MAC protocols for vehicular networks were reviewed and compared based on the scheduling technique in solving the existing challenges. The authors have noted that the mobility features of VANETs is not well considered and the merging collision issue is not well addressed which resulted in a high delay and packet loss.…”
Section: Related Workmentioning
confidence: 99%
“…Vehicles transmit the messages during the reserved time slots reducing the occurrence of message collision. Authors [17] [18] have proposed dividing the time frame as variable-sized, fixed-sized, and dynamic sized based on the system's requirements. In this paper, a variable-sized time frame division mechanism is proposed for appropriate SCH channel access.…”
Section: B Time Division Multiple Accessmentioning
confidence: 99%
“…This high mobility engenders collisions between nodes that are using the same slots and that move toward each another in addition to access collisions engendered by nodes trying to use the same time slot. Tambawal et al 25 have presented an overview on VANETs proposed TDMA based MAC protocols. They have concluded that their scheduling techniques proposed to overcome the challenges mentioned above didn't provide an effective solution to the problem of high mobility that delays and degrades the deliverance of warning messages.…”
Section: Related Workmentioning
confidence: 99%